Kendala Rekonsiliasi Dana BOS Terhadap Penyusunan LKPD Pada BPKAD Kota Magelang - Arya Dwi Saputra; Dian Rubihani (GLOBAL SCIENTS PUBLISHER, 2026)
Financial reconciliation is a crucial process in governmental accounting systems to ensure consistency between financial reports of implementing units and the records of local governments. This study aims to analyze the obstacles in the reconciliation process of School Operational Assistance (BOS) funds between schools and the Regional Financial and Asset Management Agency (BPKAD) of Magelang City, as well as its impact on the preparation of the Local Government Financial Report (LKPD). The research employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The findings reveal that the main obstacles in BOS fund reconciliation stem from limited accounting knowledge and insufficient human resources at the school level. These conditions lead to recording errors, discrepancies between reports and supporting documents, and delays in report submission. Consequently, these challenges hinder the reconciliation process and slow down the preparation of the LKPD